Risk Factors Related Amputation on Diabetic Foot Patients in Dr. M. Djamil General Hospital Padang - Eko Rizki; Raflis Rustam; Vendry Rivaldy (HM Publisher, 2022)
Backgrounds. Diabetic foot is the most common cause of nontraumatic lower-extremity amputation. This study aims to assess the relationship of risk factors with the incidence of amputation in diabetic foot patients based on the Wagner classification at Dr. M. Djamil General Hospital Padang. Methods. The study design is an analytic observational study with a cross-sectional approach. A total of 46 diabetes mellitus patients with diabetic foot complications participated in this study. The risk factors assessed were gender, age, smoking status, hypertension, uncontrolled blood sugar, hypoalbumin, peripheral arterial disease, infection, and peripheral neuropathy. The assessment of the degree of diabetic foot complications was carried out using the Wagner classification. Results. The most age group for diabetic foot sufferers is the age group of 41-60 years, which is 57.7% with the male sex being more dominant (59.6%) than the female gender. In the subject, there were more patients with the Wagner 4 classification (32.7%) than the other classification levels. Based on direct observation of patients, it was found that 53.8% of diabetic foot patients were amputated. Based on the results of the analysis, it was found that PAD (peripheral arterial disease) and peripheral neuropathy are variables that significantly affect amputation. Conclusion. Peripheral neuropathy and peripheral arterial disease are associated with amputation and peripheral arterial disease is a major risk factor for amputation in diabetic foot patients based on the Wagner classification.